Young children's buddy reading with multimodal app books: reading patterns and characteristics of readers, texts, and contexts. Issue 8 (3rd August 2018) - Christ, Tanya; Wang, X. Christine; Erdemir, Ersoy
ABSTRACT: This qualitative study investigated 27 US and 28 Turkish dyads of children between 4 and 6 years old who read 12 app books across a school year. Emergent coding and constant comparison were used to identify reading patterns in which the dyads engaged: hotspot-centric, text-centric, and integrated. Then we examined how characteristics of readers (socio-economic status, language, and gender), text (animations, navigation features, and typographical cues), and context (social interaction styles) were related to these reading patterns. Children read differently in their native versus a foreign language, and social interaction styles played a role in how reading patterns changed over time. Integrated reading, navigating sequentially through the app book, and collaborative social interactions were related to deeper meaning-making and the use of more effective reading patterns over time. Implications include how to model and scaffold app book reading practices, select texts for instruction, and design app books with features that have been shown to be effective.